If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x(3x + 6) = -22 Reorder the terms: 7x(6 + 3x) = -22 (6 * 7x + 3x * 7x) = -22 (42x + 21x2) = -22 Solving 42x + 21x2 = -22 Solving for variable 'x'. Reorder the terms: 22 + 42x + 21x2 = -22 + 22 Combine like terms: -22 + 22 = 0 22 + 42x + 21x2 = 0 Begin completing the square. Divide all terms by 21 the coefficient of the squared term: Divide each side by '21'. 1.047619048 + 2x + x2 = 0 Move the constant term to the right: Add '-1.047619048' to each side of the equation. 1.047619048 + 2x + -1.047619048 + x2 = 0 + -1.047619048 Reorder the terms: 1.047619048 + -1.047619048 + 2x + x2 = 0 + -1.047619048 Combine like terms: 1.047619048 + -1.047619048 = 0.000000000 0.000000000 + 2x + x2 = 0 + -1.047619048 2x + x2 = 0 + -1.047619048 Combine like terms: 0 + -1.047619048 = -1.047619048 2x + x2 = -1.047619048 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = -1.047619048 + 1 Reorder the terms: 1 + 2x + x2 = -1.047619048 + 1 Combine like terms: -1.047619048 + 1 = -0.047619048 1 + 2x + x2 = -0.047619048 Factor a perfect square on the left side: (x + 1)(x + 1) = -0.047619048 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 960=2x^2+4x | | -54+3x=30+7x | | -38+10x=7x+43 | | -x-91=63+6x | | 8x-90=-9x+182 | | 5x-20=10+7x | | -36+x=33-2x | | 6x+3-6x-10=x+520 | | 58=22+2 | | 7x-87=-3x+73 | | 2(-3x+2)=-38 | | 58=2+22 | | -y=2-2x | | -53+2x=-7x+109 | | 3y-7=30 | | n(3-8)2n+-4-n=48 | | 3(XH)-5x=12-(6x-7) | | 3=4-a | | 12=14.99x+79 | | 12y=14.99x+79 | | 6=4-z | | F=30000+17000t+-1000t^2 | | 5-7y=19 | | y=125x+150 | | X^2-7nX+12n^2=0 | | 15+3x+1=7x | | 5x+20y=32 | | 200+35x=25x+150 | | -5x+2.5=-3x+11 | | 6x^2-120x+45=0 | | -4x+3(x-5)=31 | | 20=-4+6y |